DETERMINATION OF ANTIBACTERIAL EFFICIENCIES OF COMMERCIAL PLANT ESSENTIAL OILS AND TANNINS AGAINST PLANT PATHOGENIC BACTERIA - C. C. Başaran; İ. Bektaş; M. Küsek (Journal of Animal and Plant Sciences, 2022)
Kahramanmaras region is suitable for pome fruits, vine and pepper cultivation. This study was conducted to evaluate the antibacterial effects of 6 different commercial essential oil (thyme, mint, cinnamon, clove, orange and ginger) and 3 different commercial tannin (Artutan, Artutan K and Farmatan) extracts against several isolates of different plant pathogenic bacterial species (Rhizobium spp. (syn. Agrobacterium), Xanthomonas spp. and Erwinia amylovora) by using disc diffusion method. Minimum Inhibitory Concentrations (MICs) was determined by using broth micro-dilution method for plant extracts which caused > 5 mm inhibition zones. Thyme and cinnamon essential oils were determined as the most effective essential oils but ginger essential oil was the least effective oil determined. The activity of essential oils also varied statistically according to bacterial species tested. The most susceptible isolate was determined Rhizobium spp. CU5-4/6 and the most resistant isolates were Xanthomonas spp. MB7-5 and MB6-3. Xanthomonas spp. isolates were found to be more resistant to essential oils than Rhizobium spp. and E. amylovora isolates. MIC value of mint and thyme essential oils against Rhizobium spp. isolates varied between 10-20 µl/ml; thyme 10 µl/ml for Xanthomonas spp. isolates and mint 20 µl / ml for Xanthomonas spp. MB6-6 isolate. MIC value of cinnamon essential oils against Rhizobium spp. isolates CU5-4/6 and CU5-4/10 was determined as 20-40 µl/ml. Clove essential oil caused inhibition at 10 µl/ml against Xanthomonas spp. isolates. Our results clearly shown that plant extracts may be used as an alternative control method in sustainable and organic farming against pathogens.
Keywords: plant pathogen bacteria; plant extracts; antibacterial activity; MIC